Evaluation of the probiotic potential of yeast isolated from kombucha in New Zealand - Wang, Boying; Rutherfurd-Markwick, Kay; Liu, Ninghui; Zhang, Xue-Xian; Mutukumira, Anthony N. (Current research in food science, 2024)
The current study investigated the in vitro probiotic potential of yeast isolated from kombucha, a tea beverage fermented with a symbiotic culture of acetic acid bacteria and yeast. A total of 62 yeast strains were previously isolated from four different commercial kombucha samples sold in New Zealand. Fifteen representative isolates belonging to eight different species were evaluated for their growth under different conditions (temperature, low pH, concentrations of bile salts, and NaCl). Cell surface characteristics, functional and enzymatic activities of the selected strains were also studied in triplicate experiments. Results showed that six strains (Dekkera bruxellensis LBY1, Sachizosaccharomyces pombe LBY5, Hanseniaspora valbyensis DOY1, Brettanomyces anomalus DOY8, Pichia kudraivzevii GBY1, and Saccharomyces cerevisiae GBY2) were able to grow under low-acid conditions (at pH 2 and pH 3) and in the presence of bile salts. This suggests their potential to survive passage through the human gut. All 15 strains exhibited negative enzymatic activity reactions (haemolytic, gelatinase, phospholipase, and protease activities), and thus, they can be considered safe to consume. Notably, two of the fifteen strains (Pichia kudraivzevii GBY1 and Saccharomyces cerevisiae GBY2) exhibited desirable cell surface hydrophobicity (64.60–83.87%), auto-aggregation (>98%), co-aggregation, resistance to eight tested antibiotics (ampicillin, chloramphenicol, colistin sulphate, kanamycin, nalidixic acid, nitrofurantoin, streptomycin, and tetracycline), and high levels of antioxidant activities (>90%). Together, our data reveal the probiotic activities of two yeast strains GBY1 and GBY2 and their potential application in functional food production. [Display omitted] •Fifteen representative yeast strains from commercial Kombucha samples sold in New Zealand were evaluated for their in vitro probiotic potential.•Pichia kudraivzevii GBY1 and Saccharomyces cerevisiae GBY2 exhibited excellent antioxidant and probiotic activities.•Data consistently show that GBY1 and GBY2 are potential probiotics suitable for application in functional foods.